2016
DOI: 10.1021/acs.chemmater.6b04122
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability, Oxygen-Storage Capability, and Electrocatalytic Activity in Solid Oxide Fuel Cells of (Y, In, Ca)BaCo4–yGayO7+δ

Abstract: With an aim of enhancing their high-temperature phase stability, oxygen-storage capability, and electrocatalytic activity in intermediate-temperature solid oxide fuel cells (IT-SOFCs), RBaCo4O 7+δ -based samples have been investigated with a co-substitution at the R site with Y, In, and Ca and Ga substitution at the Co site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Meanwhile, there are a few reports adopting Er or Ga as dopants for cathode-active materials in LIBs. While Er-doped LiFePO 4 and LiNi 0.5 Mn 1.5 O 4 showed improved cycling stability [23,24], Ga-doped layered LiN 0.6 Co 0.2 Mn 0.2 O 2 presented enhanced electrochemical performance and thermal stability, which is in line with the Manthiram group's result based on the YBC material related to the improved phase stability at high temperatures [21,25].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Meanwhile, there are a few reports adopting Er or Ga as dopants for cathode-active materials in LIBs. While Er-doped LiFePO 4 and LiNi 0.5 Mn 1.5 O 4 showed improved cycling stability [23,24], Ga-doped layered LiN 0.6 Co 0.2 Mn 0.2 O 2 presented enhanced electrochemical performance and thermal stability, which is in line with the Manthiram group's result based on the YBC material related to the improved phase stability at high temperatures [21,25].…”
Section: Introductionsupporting
confidence: 79%
“…It is well known that the swedenborgite structure (space group: P6 3 mc) of YBC with two layers of CoO 4 tetrahedral coordinates suffers from severe phase instability by thermal decomposition at 600-800 • C due to the preference of Co ions for octahedral coordination, which makes its application in SOFC difficult [19,20]. Manthiram et al reported that YBC doped with the optimum content of Ga, which substitutes for Co sites, can effectively overcome this phase instability at high temperatures of 600-800 • C [21]. Our recent work reported that Er and Ga co-doped YBC oxide (YEBCG) showed excellent phase stability compared to YBC, presenting long-term durability under reversible protonic ceramic cell conditions [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the Ga doped-YBaCo 4− y Ga y O 7+ δ ( y = 0.6–0.8) series, YBaCo 3.2 Ga 0.8 O 7+ δ exhibited good stability in long-term studies suggesting the positive effect of Ga doping to reduce the temperature range of decomposition and improving the phase stability at 800 °C. 272 On the other hand, serious decomposition of InBaCo 3.3 Ga 0.7 O 7+ δ into Co 3 O 4 , In 2 O 3 and CaBa–Co 3.3 Ga 0.7 O 7+ δ indicated again that the instability of Co 3+ in the tetrahedral sites and its preference for octahedral coordination is the cause of phase instability. 272 The Y-doped Y 1− x In x BaCo 3.3 Ga 0.7 O 7+ δ ( x = 0.1–0.9) series also remains stable at high temperatures indicating that the synergistic effect of In and Y could also maximize the stability at a certain Ga content.…”
Section: Other Crystal Structures For It-sofc Cathodesmentioning
confidence: 99%
“…272 On the other hand, serious decomposition of InBaCo 3.3 Ga 0.7 O 7+ δ into Co 3 O 4 , In 2 O 3 and CaBa–Co 3.3 Ga 0.7 O 7+ δ indicated again that the instability of Co 3+ in the tetrahedral sites and its preference for octahedral coordination is the cause of phase instability. 272 The Y-doped Y 1− x In x BaCo 3.3 Ga 0.7 O 7+ δ ( x = 0.1–0.9) series also remains stable at high temperatures indicating that the synergistic effect of In and Y could also maximize the stability at a certain Ga content. 272 However, Y 1− x Ca x BaCo 3.3 Ga 0.7 O 7+ δ and In 1− x Ca x BaCo 3.3 Ga 0.7 O 7+ δ samples were not stable long-term, suggesting that there is no synergistic effect of In and Ca codopants.…”
Section: Other Crystal Structures For It-sofc Cathodesmentioning
confidence: 99%
See 1 more Smart Citation